Radial Evolution of MHD Turbulence Anisotropy in Low Mach Number Solar Wind - Xingyu Zhu; Gary P. Zank; Lingling Zhao; Ashok Silwal (The Astrophysical Journal Letters)
The Parker Solar Probe (PSP) and Wind spacecraft observed the same plasma flow during PSP encounter 15. The solar wind evolves from a sub-Alfvénic flow at 0.08 au to become modestly super-Alfvénic at 1 au. We study the radial evolution of the turbulence properties and deduce the spectral anisotropy based on the nearly incompressible (NI) MHD theory. We find that the spectral index of the z ^+ spectrum remains unchanged (∼−1.53), while the z ^− spectrum steepens, the index of which changes from −1.35 to −1.47. The fluctuating kinetic energy is on average greater than the fluctuating magnetic field energy in the sub-Alfvénic flow while smaller in the modestly super-Alfvénic flow. The NI MHD theory well interprets the observed Elsässer spectra. The contribution of 2D fluctuations is nonnegligible for the observed z ^− frequency spectra for both intervals. Particularly, the magnitudes of 2D and NI/slab fluctuations are comparable in the frequency domain for the modestly super-Alfvénic flow, resulting in a slightly concave shape of z ^− spectrum at 1 au. We show that, in the wavenumber domain, the power ratio of the observed forward NI/slab and 2D fluctuations is  ∼15 at 0.08 au, while it decreases to  ∼3 at 1 au, suggesting the growing significance of the 2D fluctuations as the turbulence evolves in low Mach number solar wind.